PENGARUH PENGETAHUAN PERPAJAKAN, SOSIALISASI PERPAJAKAN, DAN TARIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK SEBAGAI PELAKU UMKM - Gayatri, Putu Githa; Setiawan, Putu Ery (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023DO - 10.24843/EEB.2023.v12.i12.p20, 2023)
Taxpayer compliance can be defined as the act of an individual taxpayer who complies with all his tax obligations and uses all his rights according to the applicable tax regulations. This research sought to analyze the effect of tax knowledge, tax socialization, and tax rates on Micro, Small and Medium Business (MSME) taxpayer compliance. This research was conducted at the Tax Service Office of West Denpasar. The research samples were selected through the purposive sampling method with its calculations using the Slovin formula. The subsequent calculation result using said formula obtained 100 respondents of MSME Taxpayer at the Tax Service Office of West Denpasar in 2021. The data were then analyzed using the multiple linear regression analysis. The research results revealed that tax knowledge, tax socialization, and tax rates have positive effect on MSME taxpayer compliance. As the tax knowledge possessed by the taxpayer gets higher and the tax socialization gets better, the taxpayer compliance will be better in fulfilling obligations. Furthermore, the determination of tax rates will affect and motivate taxpayers to fulfill their obligations